The Formation of Milky Way “Bones”: Ubiquitous HI Narrow Self-absorption Associated with CO Emission - Sun, Shenglan; Ke Wang; Liu, Xunchuan; Xu, Fengwei (The Astrophysical Journal Letters, 2024)
Long and skinny molecular filaments running along Galactic spiral arms are known as “bones,” since they make up the skeleton of the Milky Way. However, their origin is still an open question. Here, we compare spectral images of HI taken by the Five-hundred-meter Aperture Spherical radio Telescope (FAST) with archival CO and Herschel dust emission to investigate the conversion from HI to H2 in two typical Galactic bones, CFG028.68-0.28 and CFG047.06+0.26. Sensitive FAST HI images and an improved methodology enabled us to extract HI narrow self-absorption (HINSA) features associated with CO line emission on and off the filaments, revealing the ubiquity of HINSA toward distant clouds for the first time. The derived cold HI abundances, [HI]/[H2], of the two bones range from ∼(0.5 to 44.7) × 10−3, which reveal different degrees of HI–H2 conversion, and are similar to those of nearby, low-mass star-forming clouds, Planck Galactic cold clumps, and a nearby active high-mass star-forming region G176.51+00.20. The HI–H2 conversion has been ongoing for 2.2–13.2 Myr in the bones, a timescale comparable to that of massive star formation therein. Therefore, we are witnessing young giant molecular clouds (GMCs) with rapid massive star formation. Our study paves the way of using HINSA to study cloud formation in Galactic bones and, more generally, in distant GMCs in the FAST era.